Analysis of Granularity Adjustment for Regulatory Capital - Mario Krali; Andrey Gurov (Journal of Central Banking Theory and Practice, 2019)
The lack of portfolio granularity in terms of exposure has been shown to have important implications for the amount of a financial institution's economic capital. Based on a numerical simulation model, we provide concrete examples of how granularity affects capital levels. We achieve this by following two simulation approaches, including a dynamic setup as a more realistic version of the analysis. We show that granularity has an indirect effect on the expected loss component. This could lead to significant changes in the competitive environment should banks consider adding a granularity adjustment to the estimated amount of capital and account for it in their pricing.
Keywords: E58; G21; G28; G32; 330; Finance; Regulation; Basel; Granularity; Banks; Capital; Concentration; Risk; Corporate Exposures.